PERAN FINANCIAL CONSULTANT PT VALBURY SURABAYA DALAM MENINGKATKAN LITERASI MASYARAKAT UMUM TENTANG TRADING ONLINE - Anugerah, Novyan Noer; Saputra, Vian Ahmad (Gapenas Publisher, 2025)
The low level of financial literacy among the public, especially the younger generation, poses a high risk of errors in digital investment decisions, including online commodity trading activities. In response to this issue, a community service program by PT Valbury Surabaya was conducted to enhance prospective clients’ understanding of trading concepts, associated risks, and legal compliance. This program employed a qualitative descriptive and participatory approach, combining face-to-face education, digital media utilization, and demo account simulations. The results showed significant improvements across five literacy indicators, such as the ability to distinguish between legal and illegal platforms, awareness of risks, and increased participant interest in further learning. Trading simulations proved effective in strengthening conceptual understanding and building participants’ confidence. The activity also fostered active discussions and collective awareness of the importance of managing digital finances legally and strategically. In conclusion, this practice-based and interactive educational approach is essential for improving trading literacy and is worth expanding to broader communities as a tangible contribution to digital financial inclusion.